Discovery of carotenoid red-shift in endolithic cyanobacteria from the Atacama Desert - Vítek, Petr; Ascaso, Carmen; Artieda, Octavio; Casero, María Cristina; Wierzchos, Jacek (Scientific reports, 2017)
The biochemical responses of rock-inhabiting cyanobacteria towards native environmental stresses were observed in vivo in one of the Earth's most challenging extreme climatic environments. The cryptoendolithic cyanobacterial colonization, dominated by Chroococcidiopsis sp., was studied in an ignimbrite at a high altitude volcanic area in the Atacama Desert, Chile. Change in the carotenoid composition (red-shift) within a transect through the cyanobacteria dominant microbial community (average thickness ~1 mm) was unambiguously revealed in their natural endolithic microhabitat. The amount of red shifted carotenoid, observed for the first time in a natural microbial ecosystem, is depth dependent, and increased with increasing proximity to the rock surface, as proven by resonance Raman imaging and point resonance Raman profiling. It is attributed to a light-dependent change in carotenoid conjugation, associated with the light-adaptation strategy of cyanobacteria. A hypothesis is proposed for the possible role of an orange carotenoid protein (OCP) mediated non-photochemical quenching (NPQ) mechanism that influences the observed spectral behavior. Simultaneously, information about the distribution of scytonemin and phycobiliproteins was obtained. Scytonemin was detected in the uppermost cyanobacteria aggregates. A reverse signal intensity gradient of phycobiliproteins was registered, increasing with deeper positions as a response of the cyanobacterial light harvesting complex to low-light conditions.
Keywords: biologické pigmenty; Environmental Microbiology; Cyanobacteria; ekosystém; Ecosystem; sinice; spektrální analýza; Desert Climate; pouštní klima; konfokální mikroskopie; Microscopy, Confocal; Microscopy, Fluorescence; Pigments, Biological; Carotenoids; karotenoidy; Spectrum Analysis; mikrobiologie životního prostředí; fluorescenční mikroskopie